The The Effect of Jumping Step Up Training on Improving the Rhythm of Long Jump Takeoff of Elementary School Students - Bagus Setyo Utomo; Hilmy Aliriad; Hasan Saifuddin (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to determine the effect of jumping step-up training on increasing the takeoff rhythm in the long jump of elementary school students. Takeoff rhythm is a very important technical component because it determines the effectiveness of energy transfer from the run-up phase to the takeoff and jump phases. This study used an experimental method with a one-group pretest–posttest design with 19 elementary school students participating in physical education. The research instrument was a long jump skills test that assessed the accuracy of the takeoff rhythm, while treatment was given through jumping step-up training for eight meetings with structured intensity. Data were analyzed using a paired t-test to determine differences in results before and after treatmentThe results of the study showed a significant increase in the ability of the push-off rhythm after being given jumping step-up training. This increase is related to the increase in strength and explosive power of the leg muscles, motor coordination, rhythmic control of steps, and students' confidence when doing push-offs. Jumping step-up training is also suitable for the characteristics of elementary school students because the movements are simple, repetitive, and safe to do. Thus, jumping step-up can be recommended as an effective alternative plyometric exercise in physical education learning to improve the push-off rhythm and long jump performance of elementary school students.